Implementasi Media Sparkol Videoscribe dalam Pembelajaran Bahasa Arab untuk Meningkatkan Hasil Belajar Siswa MAN 1 Yogyakarta - Muchamad Kharis As'ad (Mahira: Journal of Arabic Studies & Teaching, 2023)
The background of this research is the lack of maximum use of learning media in teaching and learning activities in the classroom. So that learning objectives that are oriented towards improving student learning outcomes are not met properly. So this study offers one medium that can be used in helping students in the process of learning Arabic, in this case by using sparkol videoscribe learning media. The method used in this study was by designing the Pre-test Post-test Control Group Design research, which used experiment classes and control classes as subjects in this study. Based on statistical calculations that have been carried out in the experimental class and control class, a significance value of 0.005 is obtained, of which the value is included in the category of accepted. Therefore, it can be concluded that the use of sparkol videoscribe learning media can improve the learning outcomes of class X MIPA 4 MAN 1 Yogyakarta students.